Analisis Daya Saing Komoditi Crude Palm Oil (CPO) Indonesia Tahun 2001-2012 - Astrini, Ni Nyoman Ayu Puri (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
The purpose of this study is to analyze the comparative and competitive advantages Indonesian CPO compared with two OECD countries (Japan and Australia) in the period 2001-2012. This study used descriptive statistics to analyze the competitiveness of Indonesia's CPO exports in 2001-2012. The data analysis technique used in this study are revealed comparative advantage index (RCA) as well as trade specialization index (ISP). It was found that the comparative advantage of the competitiveness of the Indonesian palm oil as measured by the RCA index has an average value of 2.61 is greater than 1 and it shows that both countries have a comparative advantage for palm oil products because it has a weak level of competitiveness in the market internationally. The competitive advantage of Indonesian CPO competitiveness as measured by the Trade Specialization Index (ISPs) have an average value of 0.9989 with a value close to +1 and it's showed that Indonesian exports are at a stage of maturation, so that Indonesian palm oil products are very competitive to compete in the international market.
Keywords: Analisis Daya Saing; CPO; OECD; RCA; ISP